Lumpy Skin Disease: An Emerging Concern in Pakistan and its Impact on National Economic Loss - Hussain, Muhammad Mudasser; Khalid, Aisha; Rehman, Mujeeb Ur; Wahab, Abdul (BioScientific Review, 2024)
Lumpy Skin Disease (LSD), an emerging viral infection of cattle and buffalo, poses significant challenges to the livestock industry in Pakistan. Symptoms of this disease include enlarged appearance of lumps, high fever, discharge from the eyes and nose, and loss of appetite. The incubation period of this virus in cattle is approximately 28 days, as per the report of the Food and Agriculture Organization (FAO). This viral infection spreads through direct contact among herds. The World Organization for Animal Health (WOAH) and the FAO both warn that the spread of illnesses could lead to serious economic losses. A considerable financial loss in this industry is due to the mortality rate, reduced milk and meat production rate, and increasing management and treatment expenses. Generally, the best administrative approach to treating this disease is vaccination, which is also an economically effective strategy. This review aims to provide insights into the symptoms, risk factors, control, and disease administrative strategies, economic loss associated with Lumpy Skin Disease, and the potential role of vaccination in future disease management strategies.